Pelatihan Canva dan Linktree dalam Mendukung Pembelajaran Berbasis Teknologi - Aidil Akbar; Erlia Hanum; Mauliana Wayudi; Muslihin Muslihin; Wahyudi Wahyudi (Al-Qalam Institute, 2023)
This community service activity aims to enhance teachers' competence in creating innovative technology-based learning media. Not all teachers have sufficient understanding and skills to optimally utilize the popular and valuable Canva and Linktree applications as technology-based learning media. Through this community service activity, training will be conducted to address this issue. The participants of this community service activity consist of 30 members of the MGMP Nagan Raya. The implementation stages of this activity are divided into three main parts: preparation, execution, and evaluation. The methods used in this community service activity include observation, group discussion forums, interviews, socialization, training, and mentoring. The final result of this activity is that teachers can understand and effectively use Canva and Linktree applications to create innovative learning media. The outcomes indicate an improvement in the knowledge and skills of the training participants, namely the teachers, in using Canva and Linktree to support technology-based learning.